The Intonational Structure of Singapore English - Chow, Daryl (Université d'Ottawa / University of Ottawa, 2016)
This dissertation is a comprehensive description of the structure of the prosody of Singapore English. Using the Prosodic Hierarchy as a framework, each layer of the structure of Singapore English is described in detail. The smallest level described in this dissertation is the syllable, the domain in which the majority of segmental processes occur in Singapore English. The second level is the prosodic word domain, where there is a high tone anchored to the final syllable and a low tone anchored to the left edge, and these tones are shown in this dissertation to be recursive. These tones are independent of stress, which is argued to not exist in Singapore English. The third level is the intonational phrase, where the final syllable carries the boundary tone of the entire intonational phrase, affecting the tones of final particles. There is also a phrase-initial boost on the first prosodic word of the intonational phrase. Markedly absent is any intermediate phrase or domain between the word and intonational phrase, which is argued to not exist in this dissertation. The dissertation ends with a look at the possible origins of the prosody of Singapore English and a consideration of the prosodic systems which may have influenced its development.
Keywords: Phonology; Prosody; English; Tone